High Tibial Osteotomy: State of the art - Mustamsir, Edi; Sukmajaya, William Putra (The Hip and Knee Journal, 2023)
The number of cases handled by PJI is projected to rise in the coming years. The diagnosis of PJI relies on evaluating microbiology, inflammatory response, and pathology. However, the accuracy of the diagnosis is compromised by previous exposure to antimicrobial agents, the possibility of contamination, and the lack of specificity of inflammatory markers. Although new testing methods, such as molecular techniques, hold the potential for a swift diagnosis, they are constrained by the risk of contamination and the absence of susceptibility results. Interestingly, emerging synovial fluid markers exhibit promise as an additional tool in diagnosing PJI. The management of each PJI case, both in terms of surgery and antimicrobial treatment, requires an individualized assessment. It is imperative to conduct high-quality studies that aim to determine the most effective route and duration of antimicrobial treatment for each surgical approach.  This review provides an overview of the diagnostic tests and treatment options for prosthetic joint infection, offering a practical approach to managing this complex clinical condition.